Penanda Kohesi Gramatikal dan Leksikal pada Wacana Narasi dalam Buku Teks Cakap Berkomunikasi dalam Bahasa Indonesia Kelas VII dan Kelayakannya sebagai Bahan Ajar - Sukma Pujiati, Klara, Dra. Atiqa Sabardila, M. Hum (2017)
This study to describe: (1) cohesive narrative discourse supported by aspects of grammatical cohesion in textbooks of Cakap Berkomunikasi dalam Bahasa Indonesia Kelas VII, (2) cohesive narrative discourse supported by the lexical cohesion aspect in textbooks of Cakap Berkomunikasi dalam Bahasa Indonesia Kelas VII, (3) the feasibility of narrative discourse in the textbook of Cakap Berkomunikasi dalam Bahasa Indonesia Kelas VII as a teaching material in junior high school. This research uses qualitative research type with approach of content study. The results of this study indicate the existence of the discourse of narrative discourse namely (1) the markers of grammatical cohesion found consisting of 34 sets or 30.0%; 26 replacements or 23.0%; 18 assignments or 16.0%; and the 6 release or 5,3%. The meanings of the series along with the conjunctions derived from this research are causal, contradictory, exceptional, conscientious, objectives, additions, choices, sequences, times, and requirements. (2) The use of the highest repetition lexical cohesion marker of 9 or 8%; antonymy of 8 or 7.0%; synonymy 7 or 6.2%; collocation of 3 or 2.7%; and hyponymy 2 or 1.8%. (3) The result of feasibility analysis of narrative discourse is assessed by researchers in terms of accuracy of the use of grammatical and lexical cohesion marker is 105 data from 113 data or as much as 92,8% of the overall percentage.